Clinical characteristics of smoking-related chronic pancreatitis - Hao, Lu; Liu, Yu; Dong, Zhi-Qi; Yi, Jin-Hui; Wang, Dan; Xin, Lei; Guo, Hong-Lei; He, Lin; Bi, Ya-Wei; Ji, Jun-Tao; Wang, Teng; Du, Ting-Ting; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Objective: The pathogenesis of chronic pancreatitis (CP) is incompletely understood. With the in-depth researches, smoking has a toxic effect on pancreas. This study classified smoking-related CP as a new etiology of CP, and defined the cutoff of smoking. Design: CP patients admitted to our center from January 2000 to December 2013 were enrolled. Characteristics were compared between smoking patients, drinking patients and group of patients who never smoke or drink (control group). Cumulative rates of diabetes mellitus (DM), steatorrhea, pancreatic stone, pancreatic pseudocyst (PPC), and biliary stricture after the onset of CP were calculated, respectively. Results: A total of 1,324 patients were enrolled. Among them, 55 were smoking patients, 80 were drinking patients, and 1,189 were controls. Smokers are different from the other two groups in many aspects, especially in age at the onset and diagnosis of CP, initial manifestation, and type of pain. The development of DM (P = 0.011), and PPC (P = 0.033) were significantly earlier and more common in the smokers than the other two groups. Steatorrhea also developed significantly more in the smokers than in the controls (P = 0.029). Smokers tend to delay the formation of pancreatic stones and steatorrhea. Conclusion: The clinical course of smoking-related CP is different from that caused by other etiologies. A new type of CP, smoking-related CP was put forward. Smoking-related CP should be separated from idiopathic CP and defined as a new independent subtype of CP different from alcoholic CP or idiopathic CP.